TINJAUAN BAURAN PEMASARAN DI PT BANK SYARIAH INDONESIA KANTOR CABANG GRAHA PARAMITA II BINTARO - Fanyta Agna Tasya, (2023)
This study aims to identify a marketing mix strategy at PT Bank Syariah Indonesia KC Graha Paramita II Bintaro. The research methodology used is qualitative analysis which is described descriptively. This study uses interviews as a means to collect data. Based on the results of the study it is known that PT Bank Syariah Indonesia KC Graha Paramita II Bintaro carries out direct marketing through the implementation of a Marketing Mix strategy consisting of the 7P concept: Product, Price, Place, Promotion, People, Process and Physical Evidence.